Circumcision-related tragedies seen in children at the Komfo Anokye Teaching Hospital, Kumasi, Ghana. Issue 1 (December 2016) - Appiah, Kwaku; Gyasi-Sarpong, Christian; Azorliade, Roland; Aboah, Ken; Laryea, Dennis; Otu-Boateng, Kwaku; Baah-Nyamekye, Kofi; Maison, Patrick; Arthur, Douglas; Antwi, Isaac; Frimpong-Twumasi, Benjamin; Yenli, Edwin; et al.
Abstract Background Circumcision is a common minor surgical procedure and it is performed to a varying extent across countries and religions. Despite being a minor surgical procedure, major complications may result from it. In Ghana, although commonly practiced, circumcision-related injuries have not been well documented. This study is to describe the scope of circumcision-related injuries seen at the Komfo Anokye Teaching Hospital in Kumasi, Ghana. Methods The study was conducted at the Urology Unit of the Komfo Anokye Teaching Hospital in Kumasi. Consecutive cases of circumcision-related injuries seen at the unit over an 18 month period were identified and included in the study. Data was collected using a structured questionnaire. Data was entered and analysed using SPSS version 16. Charts and tables were generated using Microsoft Excel. Results A total of 72 cases of circumcision-related injuries were recorded during the 18 month period. Urethrocutaneous fistula was the commonest injury recorded, accounting for 77.8 % of cases. Other injuries recorded were glans amputations (6.9 %); iatrogenic hypospadias (5.6 %), and epidermal inclusion cysts (2.8 %). The majority of children were circumcised in health facilities (75 %) and nurses were the leading providers (77.8 %). The majority of circumcisions were conducted in the neonatal period (94.7 %). Conclusion Circumcision-related injuries commonly occurred in the neonatal period. Most of the injuries happened in health facilities. The most common injury recorded was urethrocutaneous fistula but the most tragic was penile amputation. There is the need for education and training of providers to minimise circumcision-related injuries in Ghana.